The Social Educational Values in the Book ‘Iqd Al Jawāhir Creation of Syekh Ja’far Al Barzanji - Khoirini, Khoirini; Salminawati, Salminawati; Budianti, Yusnaili (Graduate Program Magister Manajemen Pendidikan, 2023)
The purpose of this research is to describe the values of social education in the book 'Iqd Al Jawāhir and to find out the implementation of the values of social education in the book 'Iqd Al Jawāhir. The research method used is content analysis because this research is a study of the text contained in the book 'Iqd Al Jawāhir through a qualitative analysis approach. This research places more emphasis on the strength of data analysis on data sources obtained from books, writings or so-called literature studies and by relying on existing theories to be interpreted broadly and deeply. Based on the research results, that the values of social education in the book 'Iqd Al Jawāhir by Syekh Jaafar Al Barzanji are: First: The value of social education contained in the book 'Iqd Al Jawāhir includes the following social values: piety to Allah, love of the prophet Muhammad, carrying out social ethics which includes: ethics in association, rights to children, rights to parents and family, to the profession, and honest morals in delivery, morals in choosing a partner, qona'ah, patience, resignation, ethics of saying good and giving moral greetings, do not belittle others.Second: The implementation of the moral values contained in 'Iqd Al Jawāhir is reflected in that a teacher must have the characteristics of the Prophet Muhammad, and teach them to his students. namely honest, merciful, forgiving, friendly, kind, and ascetic. To carry out tasks (efforts) in instilling morals in students there are many ways that every educator can do through various attitudes, including: Associating, Providing role models, Inviting and practicing.